2017
DOI: 10.1016/j.dib.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Data characterizing the genomic structure of the T cell receptor (TRB) locus in Camelus dromedarius

Abstract: These data are presented in support of structural and evolutionary analysis of the published article entitled “The occurrence of three D-J-C clusters within the dromedary TRB locus highlights a shared evolution in Tylopoda, Ruminantia and Suina” (Antonacci et al., 2017) [1]. Here we describe the genomic structure and the gene content of the T cell receptor beta chain (TRB) locus in Camelus dromedarius. As in the other species of mammals, the general genomic organization of the dromedary TRB locus consists of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(60 citation statements)
references
References 8 publications
2
58
0
Order By: Relevance
“…An analysis of the genomic sequence revealed that the general structural organization of the pig TRB locus follows that of the other mammalian species, with a library of TRBV genes positioned at the 5′ end of D-J-C clusters, followed by a single TRBV gene located at the 3′ end in an inverted transcriptional orientation (Figure 1 ). Specifically, analysis of the assembly confirmed the presence of three D-J-C clusters similar to the clusters found in other species of artiodactyls, where D-J-C cluster 3 lies between D-J-C cluster 1 and D-J-C cluster 2 ( 5 , 8 , 9 ) The pig D-J-C region covers approximately 27 kb. D-J-C cluster 1 spans 7,659 bp and contains one TRBD, seven TRBJ and one TRBC genes.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…An analysis of the genomic sequence revealed that the general structural organization of the pig TRB locus follows that of the other mammalian species, with a library of TRBV genes positioned at the 5′ end of D-J-C clusters, followed by a single TRBV gene located at the 3′ end in an inverted transcriptional orientation (Figure 1 ). Specifically, analysis of the assembly confirmed the presence of three D-J-C clusters similar to the clusters found in other species of artiodactyls, where D-J-C cluster 3 lies between D-J-C cluster 1 and D-J-C cluster 2 ( 5 , 8 , 9 ) The pig D-J-C region covers approximately 27 kb. D-J-C cluster 1 spans 7,659 bp and contains one TRBD, seven TRBJ and one TRBC genes.…”
Section: Resultssupporting
confidence: 68%
“…The TRBD, TRBJ and TRBC genes were annotated, according to the similarity with the other artiodactyl species ( 5 , 8 , 9 ). Each TRBJ1, TRBJ2, and TRBJ3 gene was designed by a hyphen and a number corresponding to their position in the cluster.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(dromedary TRB locus contig as characterized by [14][15]; NC_010460 (pig TRB locus contig as characterized by [16]); and NC_030811.1 (this work) (goat TRB locus contig). We combined the nucleotide sequences of the V-REGION of the goat TRBV genes with the corresponding gene sequences of sheep, pig and dromedary.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…In human, mouse, and several other mammals (https://www.imgt.org/IMGTrepertoire/: Homo sapiens, Mus musculus; [7,8,9,10,11]), two TRBD-J-C clusters have been identi ed. In contrast, in the artiodactyl lineage [12,13,14,15,16,17], a duplication event within the 3′ end of the TRB locus has led to the generation of a third TRBD-J-C cluster. Moreover, ruminants appear to have an increased number of genes in the TRBV gene pool, which is the largest in cattle (134 TRBV genes) [13], and sheep (94 TRBV genes) [11] and resulted from massive expansion of mainly two TRBV gene subgroups.…”
Section: Introductionmentioning
confidence: 99%